Effect of Graded Levels of Spirulina (Arthropsira platensis) on Feed Intake and in vivo Digestibility of Trypsacum laxum in Guinea Pig (Cavia Porcellus L) - Généviève Nguedia; Emile Miégoué; Fernand Tendonkeng; Mouchili Mama; Camara Sawa; Henry Feulefack Defang; Et Etienne Tedonkeng Pamo (Journal of Zoological Research, 2019)
The intake and in vivo digestibility of Trypsacumlaxum in guinea pigs according to the graded level of spirulina was evaluated in Cameroon. 20 animals aged of 6 months with an average weight of 450 ± 50 g were randomly divided into 4 equivalent groups. Each group received T. laxum and 40g of compound feed containing 0% (TS0), 2% (TS2), 4% (TS4), and 6% (TS6) of spirulina. Feed intake was the different between the left over and the quantity served. The sample of T. laxum and those of each diet as well as feces were collected and analyzed for the apparent digestibility of each nutrient. Animals were weighed at the beginning and at the end of each period of the test to determine the body weight gain. This study showed that the average daily intake of dry matter (DM) for TS0, TS2, TS4 and TS6 was 74.39 ± 2.98, 78.66 ± 3.14, 83.89 ± 4.28 and 77.76 ± 4.40 g/head/day. The highest apparent digestibility coefficients of different nutrients were obtained with animals fed TS6 group while the lowest were observed in TS0.The apparent digestibility coefficient of dry matter (DM), organic matter (OM) and crude protein (CP) of the supplemented group were statistically higher than those of the control diet. Animals’ weight performances were statistically comparable between treatments. Thus, the combination of T. laxum with concentrated feed containing spirulina can be recommended for guinea-pigs, but the level of incorporation may not exceed 4% of its daily ration.
Keywords: Arthropsira platensis